Patient preferences in obstructive sleep apnea—a discrete choice experiment - Braun, Marcel; Dietz-Terjung, Sarah; Taube, Christian; Schoebel, Christoph (Sleep & breathing, 2022)
Background Obstructive sleep apnea (OSA) is one of the most common chronic sleep disorders, which can be treated by different interventions. It is known that acceptance and adherence to these therapies is influenced by a variety of factors. However, there is a limited understanding of patient preferences and decision-making in the context of OSA treatment. Methods A discrete choice experiment was conducted on patients with OSA recruited from a tertiary sleep center to evaluate preferences for different treatment attributes. Participants received four different choice tasks with three hypothetical treatments, each defined by seven attributes. A random-effects logit model was used to estimate the influence of the different attributes on the choice decisions. Multivariate logistic regression analysis was carried out to evaluate interactions with medical variables. Results In a cohort of 241 subjects with OSA, preferences for treatment attributes and utilities derived from them differed. Most relevant attributes were Reduction in risk of comorbidities , Improvements of daytime sleepiness , Requirement for surgery , and Occurrence of treatment-related side effects . Demographic or medical variables, such as age, gender, or apnea–hypopnea index, did not influence the choice decision. Multivariate logistic regression revealed significant differences in preferences depending on OSA disease history ( p = .025) and presence of OSA symptoms ( p = .033). Conclusions The study identified preferences for attributes of OSA and their utilities from a patient perspective. Relevant differences of preferences in subgroups of patients with OSA were identified, which may be important to consider in selecting appropriate treatments that lead to high rates of acceptance and adherence.